Total revenue forecasting at BUMDEs using single moving average method - Made Hanindia Prami Swari; Hendra Maulana; I Putu Susila Handika; I Kadek Susila Satwika (Jurnal Mantik, 2023)
The use of various information systems in supporting daily business activities has become common today, including the use of a financial recording system in BumDes Sarining Winangun Kukuh that has been built. However, to support managerial decision making, a profit/loss forecasting system is needed as a basis for making future business strategies. For this reason, this research develops a profit/loss forecasting system using the Simple Moving Average method. Based on testing the accuracy of forecasting using the MAPE method, the results show that the average error rate generated is 23.53% by using financial data for 1 year, where the smallest error rate is around 4%, while the highest error rate reaches a value of 0.632 or around 63.2%, so that it can help BUMDes in knowing total revenue forecasting.